Recipes for success: Conditions for knowledge transfer across open innovation ecosystems. (December 2019) - Bacon, Emily; Williams, Michael D.; Davies, Gareth H.
Highlights: Examines conditions for knowledge transfer success between organizational partners within an open-innovation ecosystem. Employs an fs QCA approach to analyse empirical data captured from ecosystem partners. Results reveal combinations of conditions required for knowledge transfer success between ecosystem partners. Differing condition combinations are present within equally successful, ecosystem partnerships. Combinations are dependent on the type of ecosystem partnership under consideration. Abstract: Open innovation ecosystems involve the transfer of knowledge between multiple stakeholders to contribute toward product and service innovation, and to an extent, have superseded network-level approaches to co-creation. Effective management of the knowledge and information transferred between ecosystem partners is crucial for the process of open innovation. However, to date, limited research has focused on ascertaining the conditions required for knowledge transfer success, particularly where the context involves collaboration between diverse organizational actors. Correspondingly, this study extends existing knowledge by presenting an exploration of conditions for knowledge transfer success between ecosystem partners. Semi-structured interviews were conducted with thirty key stakeholders in order to acquire their perceptions of the presence of specific conditions within their ecosystem partnerships. Empirical data were analyzed using a fuzzy-set Qualitative Comparative Analysis approach, resulting in the production of success recipes from multinational, small and medium-sized enterprise, and academic institution perspectives. Results indicate that combinations of knowledge, relationship, and organizational characteristics contribute to knowledge transfer success. However, these combinations are found to be dependent on the type of ecosystem partnership involved. Theoretical and practical implications of the study are presented, along with acknowledged limitations and suggestions for further work.